Respon Dunia Barat Terhadap Ekonomi Syariah Dalam Perspektif Idiologis, Akademis Dan Pragmatis; Antara Peluang Dan Tantangan Era 4.0 - Nurjamil, Nurjamil; Syarif, Nurrohman (Program Studi Ekonomi Syariah Institut Manajemen Koperasi Indonesia, 2024)
The goal of this research is to describe and analyze the Western world's response to the development of the Islamic economy, which is examined from the standpoints of idiologic, academic and pragmatic between opportunities and challenges in era 4.0.. The method used in this study is a qualitative approach in which researchers try to find and find qualitative secondary data sourced from books, scientific journals, research results, and articles published both online and in print to then be analyzed normatively (descriptive qualitative). The findings of this study show that, in the eyes of fundamentalist political or ideological, the western response to the development of the Islamic economy is viewed as a political opponent to the continuation of wars and hostilities with Islamophobic weapons bearing the stamps of terrorism, radicalism, backwardness, and other negative attributes. According to moderate thinkers in academic perspective, Islamic economics is a test to see who can solve problems related to welfare, civilization, and other global issues. From a business standpoint or the pragmatic side, the Islamic economy is regarded as a great opportunity because the development of the Muslim population and world sympathy, which is increasingly oriented to the Islamic economy, which is regarded as more fair, profitable, carries minimal risk, and contains benefits, is a necessity, so they are forced to follow the mainstream of the world community to play in the system to take advantage, which, of course, must be suspected that religious interests remain the primary concern.